'Secondary prevention' against female HPV infection: literature review of the role of carrageenan. Issue 9 (1st September 2020) - Calagna, Gloria; Maranto, Marianna; Paola, Consiglio; Capra, Giuseppina; Perino, Antonino; Chiantera, Vito; Cucinella, Gaspare
ABSTRACT: Introduction : Human papillomaviruses (HPVs) are common sexually transmitted pathogens, causally associated with cervical cancer and other anogenital cancers, as well as approximately 20% of head and neck cancers. The HPV vaccine is an exceptional primary prevention tool, but the question of adequate secondary-prevention strategies remains open. The aim of this review is to better clarify the role of carrageenan in HPV prevention-strategies. Areas covered : A comprehensive literature search was performed (PubMed/MEDLINE, Embase, Google Scholar, Cochrane Databases) to identify articles on the use of carrageenan against HPV infection. The studies were identified using combinations of the search terms 'carrageenan, ' 'papillomavirus, ' 'HPV, ' including only English language papers. Expert opinion : Our review data confirmed the 'inhibitory role' of carrageenan against HPV- pseudoviruses infection on different cell types. The most accredited mechanism to explain this effect involves the direct binding of CG to the viral capsid creating a 'physical' obstacle. However, a different susceptibility to carrageenan for different HPV types has been highlighted, suggesting the possibility of other strategies to infect the host. There are also relevant emerging data regarding the possible role of carrageenan as an adjuvant for antigen-specific immune responses and antitumor effects.